Phosphahelicenes with (Thio)Phosphinic Acid and Ester Functions by the Oxidative Photocyclisation Approach. Issue 68 (7th November 2019) - Febvay, Julie; Demmer, Charles S.; Retailleau, Pascal; Crassous, Jeanne; Abella, Laura; Autschbach, Jochen; Voituriez, Arnaud; Marinetti, Angela
Abstract: Phosphahelicenes with thiophosphinic acid and ester functions have been obtained by the oxidative photocyclisation of olefins bearing both a benzophenanthrene and a benzophosphole unit. When the method has been extended to olefins bearing a partially saturated benzophospholene unit, a divergent regioselectivity of the photocyclisation step has been observed, leading to new helicenes in which the phosphorus function is located on the external rim of the helical backbone. The observed regioselectivity correlates well with the free‐valence numbers of the atoms involved in the photocyclisation reaction (DFT calculations). Abstract : Chirality : Phosphahelicenes with thiophosphinite functions are produced via the Mallory oxidative photocyclisation approach. Phosphole and phospholene units activate different positions of the olefinic substrates, thus leading to helicenes terminated by a meta ‐fused phosphole and an ortho ‐fused phospholene ring, respectively (see scheme).